Low-temperature cyclized polyacrylonitrile-coated manganese dioxide positive electrode material and preparation method thereof

CN122992035APending Publication Date: 2026-10-27JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611244076.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]现有研究多采用碳包覆、表面改性等手段,但常规高温碳包覆(>500℃)易导致二氧化锰相变或分解,降低材料的实际容量,且能耗高、工艺复杂

Benefits of technology

[0019]本发明针对MnO2作为水系锌离子电池正极材料的固有缺陷,提出了一种低温环化聚丙烯腈(PAN)直接包覆改性技术。低温热处理工艺,采用两段式低温处理(空气预氧化+惰性气氛深度环化、不碳化),全程温度不高于300℃,远低于传统碳包覆的500-800℃高温碳化温度。PAN非碳化利用,打破了PAN仅作为碳源的传统认知,不是将PAN高温碳化转化为碳纤维,而是通过低温环化反应使其形成具有共轭结构的稳定聚合物层。环化PAN与MnO2表面通过Mn-O-C和Mn-N共价键实现化学结合,而非简单的物理吸附或机械混合。在整个制备过程中,严格保持MnO2的隧道晶体结构,无杂相生成,也无MnO2分解现象。形成以MnO2为核、环化PAN为壳的均匀核壳结构,包覆层厚度可控(2–20 nm),得到低温环化PAN@MnO2正极材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992035A_ABST
    Figure CN122992035A_ABST
Patent Text Reader

Abstract

The application discloses a low-temperature cyclized polyacrylonitrile-coated manganese dioxide positive electrode material, which comprises manganese dioxide particles, the surface of the manganese dioxide particles is provided with a coating layer, the coating layer is cyclized polyacrylonitrile, and the coating layer and the manganese dioxide are chemically bonded through Mn-O-C and Mn-N chemical bonds. The application further discloses a preparation method of the low-temperature cyclized polyacrylonitrile-coated manganese dioxide positive electrode material, wherein MnO2 is added into a polyacrylonitrile solution for grinding, the obtained paste is ultrasonically treated, scraped into a thin layer, and dried to obtain a precursor powder; the precursor powder is heated, the temperature is raised to 180-200 DEG C at a rate of 1 DEG C / min, then the temperature is raised to 240-260 DEG C at a rate of 0.5 DEG C / min to complete pre-oxidation, finally, the temperature is raised to 280-300 DEG C at a rate of 2 DEG C / min in an inert atmosphere to complete deep cyclization, and the low-temperature cyclized polyacrylonitrile-coated manganese dioxide is obtained. The composite positive electrode manganese dioxide material obtained by the application can inhibit the dissolution of manganese in a water-based zinc ion battery and improve the cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy storage materials, and relates to a manganese dioxide cathode material suitable for aqueous zinc-ion batteries, and more particularly to a low-temperature cyclized polyacrylonitrile-coated modified manganese dioxide nanocore-shell structure cathode material and its preparation method. Background Technology

[0002] With the rapid development of the new energy storage industry, traditional lithium-ion batteries suffer from problems such as resource scarcity and poor safety, while lead-acid batteries are plagued by heavy metal pollution, making it difficult to meet the demands of large-scale energy storage. Aqueous zinc-ion batteries, due to their abundant zinc resources, low cost, and high theoretical capacity, combined with safe and non-toxic aqueous electrolytes, offer both high safety and environmental friendliness, making them a research hotspot for new energy storage batteries.

[0003] Manganese dioxide materials have been extensively explored due to their high theoretical specific capacity, high power capacity, low cost, and inherent safety with water-based electrolytes. However, their practical application still faces some key bottlenecks. During charge and discharge processes, Mn... 3+ The Jahn-Teller effect leads to structural distortion, making the tunnel structure prone to collapse. Combined with manganese dissolution caused by the disproportionation reaction, this results in rapid capacity decay and loss of active material. Byproducts easily form on the electrode surface, increasing interfacial impedance and reducing rate performance.

[0004] Existing research primarily employs methods such as carbon coating and surface modification. However, conventional high-temperature carbon coating (>500℃) easily leads to phase transformation or decomposition of manganese dioxide, reducing the actual capacity of the material, and is also energy-intensive and complex. Physical coating or simple composites exhibit weak interfacial bonding, making it difficult to fundamentally suppress manganese leaching and structural collapse. Therefore, proposing a modification method that can both preserve the crystalline phase and high capacity characteristics of manganese dioxide and construct strong interfacial bonding to effectively prevent structural collapse is of great significance for aqueous zinc-ion battery cathode materials.

[0005] To address the aforementioned problems, this invention is proposed. Summary of the Invention

[0006] To address the aforementioned technical problems in the prior art, this invention provides a low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material and its preparation method. This low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material and its preparation method aim to solve the problem of Mn content during the charging and discharging process of manganese dioxide materials in the prior art. 3+ The Jahn-Teller effect causes structural distortion, making the tunnel structure prone to collapse. In addition, the dissolution of manganese caused by the disproportionation reaction leads to technical problems such as rapid capacity decay.

[0007] This invention provides a low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material, comprising manganese dioxide particles, the surface of which has a coating layer, the coating layer being cyclized polyacrylonitrile, and the coating layer being chemically bonded to the manganese dioxide via Mn-OC and Mn-N bonds.

[0008] Furthermore, the coating layer has a thickness of 2-20 nm.

[0009] Furthermore, the mass ratio of manganese dioxide to polyacrylonitrile is from 9:1 to 19:1.

[0010] This invention also provides a method for preparing a low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material, comprising the following steps:

[0011] Step 1: First, completely dissolve polyacrylonitrile in a polar organic solvent. Then, add manganese dioxide to the polyacrylonitrile solution and grind it to obtain a uniform paste. After ultrasonic treatment of the paste, scrape it into a thin layer and dry it in a vacuum environment at 60°C to obtain the precursor powder.

[0012] Step 2: Heat the precursor powder at a heating rate of 1℃ / min until it reaches 180℃~200℃.

[0013] Step 3: Continue heating the precursor powder at a rate of 0.5℃ / min until it reaches 240~260℃. After heating, hold the temperature for 2~3 hours and then cool to obtain the pre-oxidized product.

[0014] Step 4: The pre-oxidized product is heated in an inert gas environment at a heating rate of 2℃ / min to 280℃~300℃, held for 1~2 hours, and then naturally cooled to obtain manganese dioxide coated with low-temperature cyclized polyacrylonitrile.

[0015] Furthermore, the mass ratio of manganese dioxide to polyacrylonitrile in step one is 9:1 to 19:1.

[0016] Furthermore, the polar organic solvent mentioned in step one is N,N-dimethylformamide.

[0017] Furthermore, the inert gas mentioned in step four is argon.

[0018] The present invention also provides the application of the above-mentioned low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material in aqueous zinc-ion batteries.

[0019] This invention addresses the inherent defects of MnO2 as a cathode material in aqueous zinc-ion batteries by proposing a low-temperature cyclization polyacrylonitrile (PAN) direct coating modification technology. The low-temperature heat treatment process employs a two-stage low-temperature treatment (air pre-oxidation + inert atmosphere deep cyclization, without carbonization), with the temperature throughout not exceeding 300℃, far lower than the 500-800℃ high-temperature carbonization temperature of traditional carbon coating. The non-carbonization utilization of PAN breaks with the traditional understanding of PAN as merely a carbon source; instead of converting PAN into carbon fibers through high-temperature carbonization, it forms a stable polymer layer with a conjugated structure through a low-temperature cyclization reaction. The cyclized PAN and the MnO2 surface achieve chemical bonding through Mn-OC and Mn-N covalent bonds, rather than simple physical adsorption or mechanical mixing. Throughout the entire preparation process, the tunnel crystal structure of MnO2 is strictly maintained, with no impurity phase formation or MnO2 decomposition. A uniform core-shell structure with MnO2 as the core and cyclized PAN as the shell is formed, and the coating thickness is controllable (2–20 nm), resulting in a low-temperature cyclized PAN@MnO2 cathode material.

[0020] Compared with existing technologies, the technical effects of this invention are positive and significant. This invention completely solves the problem of high-temperature modification damaging the MnO2 crystal phase. Conventional carbon coating and PAN high-temperature carbonization routes require high-temperature treatment above 500℃, which leads to irreversible phase transformation or decomposition of MnO2, destroying its unique tunnel structure and significantly reducing the initial specific capacity of the material. This solution uses a low-temperature treatment process not exceeding 300℃, completely avoiding the crystal phase transformation of MnO2 and fully preserving its high theoretical capacity structural basis. It achieves strong interfacial bonding and inhibits manganese leaching. Existing technologies, such as physical coating, simple composite, and high-temperature carbonization, only achieve weak physical bonding between carbon fibers and MnO2, resulting in poor interfacial bonding. The coating layer is prone to detachment during charge and discharge, failing to effectively prevent direct contact between the electrolyte and MnO2 for a long period, and the structural collapse problem remains serious. This invention achieves chemical anchoring through Mn-OC and Mn-N covalent bonds, forming a stable chemical bond connection between the coating layer and the matrix, significantly enhancing the interfacial bonding. This strong interfacial effect can alleviate the structural collapse problem during charge and discharge. This solution employs a simple process flow of solution dispersion, drying, and two-stage low-temperature heat treatment. It requires no complex equipment or expensive reagents, has a short production cycle, low energy consumption due to the low-temperature treatment throughout the process, good compatibility with existing lithium battery cathode material production processes, and is easy to scale up industrially. Attached Figure Description

[0021] To more clearly illustrate the technical solution of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a scanning electron microscope image of the manganese dioxide material prepared in Comparative Example 1 of the present invention.

[0023] Figure 2 This is a transmission electron microscope image of the 10% P@MnO2 composite material prepared in Example 2 of the present invention.

[0024] Figure 3 The images show the XRD patterns of the 5% P@MnO2 composite material prepared in Example 1, the 10% P@MnO2 composite material prepared in Example 2, the 20% P@MnO2 composite material prepared in Example 3, and the MnO2 material prepared in Comparative Example 1.

[0025] Figure 4 XPS images of oxygen and nitrogen elements in the 10% P@MnO2 material prepared in Example 2 of this invention.

[0026] Figure 5 Cyclic stability graphs of the 5% P@MnO2 composite material prepared in Example 1, the 10% P@MnO2 composite material prepared in Example 2, the 20% P@MnO2 composite material prepared in Example 3, and the MnO2 material prepared in Comparative Example 1.

[0027] Figure 6 The graphs show the rate cycling performance of the 10% P@MnO2 composite material prepared in Example 2 and the MnO2 material prepared in Comparative Example 1 at different current densities. Detailed Implementation

[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1

[0030] Weigh out 0.95 g of MnO2 and 0.05 g of polyacrylonitrile (PAN). First, dissolve PAN in 5 mL of N,N-dimethylformamide and stir until completely dissolved. Add MnO2 to the PAN solution in three portions, grinding for 10 minutes after each addition in an agate mortar. After all the MnO2 has been added, continue grinding for 30 minutes to obtain a uniform paste. Then transfer the paste to a glass bottle and sonicate it for 30 minutes in an ultrasonic cleaner. Pour the paste onto a polytetrafluoroethylene plate, scrape it into a 1 mm thick layer with a scraper, and vacuum dry at 60°C for 12 hours to obtain the precursor powder.

[0031] The precursor powder was placed in a quartz boat and then placed in a muffle furnace.

[0032] In the first stage, the heating rate is 1℃ / min, and the temperature is raised to 180℃.

[0033] In the second stage, the temperature was increased from 180℃ to 260℃ at a rate of 0.5℃ / min. The temperature was maintained for 2 hours, and the product was obtained after cooling.

[0034] The pre-oxidized product was heated to 280°C at a rate of 2°C / min in an argon atmosphere and held at that temperature for 1 hour. After natural cooling, the final material was obtained, denoted as 5% P@MnO2.

[0035] Polyacrylonitrile@manganese dioxide, conductive agent acetylene black, and binder polyvinylidene fluoride were mixed and ground at a mass ratio of 7:2:1, and then coated onto a carbon cloth current collector. The mixture was dried at 80°C for 24 hours to obtain a polyacrylonitrile@manganese dioxide modified cathode material. An aqueous zinc-ion battery was assembled using commercial zinc sheets as the negative electrode, 2 mol / L zinc sulfate as the electrolyte, and a glass fiber membrane as the separator.

[0036] Example 2

[0037] Weigh out 0.9 g of MnO2 and 0.1 g of PAN. First, dissolve the PAN in 10 mL of DMF and stir until completely dissolved. Add the MnO2 to the PAN solution in three portions, grinding for 10 minutes after each addition in an agate mortar. After all the MnO2 has been added, continue grinding for 30 minutes to obtain a uniform paste. Then transfer the paste to a glass bottle and sonicate it in an ultrasonic cleaner for 30 minutes. Pour the paste onto a polytetrafluoroethylene plate, scrape it into a 1 mm thick layer with a scraper, and vacuum dry at 60°C for 12 hours to obtain the precursor powder.

[0038] The precursor powder was placed in a quartz boat and then placed in a muffle furnace.

[0039] In the first stage, the heating rate is 1℃ / min and the temperature is 180℃.

[0040] In the second stage, the temperature was increased from 180℃ to 260℃ at a rate of 0.5℃ / min. The temperature was maintained for 2 hours, and the product was obtained after cooling.

[0041] The pre-oxidized product was heated to 280°C at a rate of 2°C / min in an argon atmosphere and held at that temperature for 1 hour. After natural cooling, the final material was obtained, denoted as 10%P@MnO2.

[0042] Polyacrylonitrile@manganese dioxide, conductive agent acetylene black, and binder polyvinylidene fluoride were mixed and ground at a mass ratio of 7:2:1, and then coated onto a carbon cloth current collector. The mixture was dried at 80°C for 24 hours to obtain a polyacrylonitrile@manganese dioxide modified cathode material. An aqueous zinc-ion battery was assembled using commercial zinc sheets as the negative electrode, 2 mol / L zinc sulfate as the electrolyte, and a glass fiber membrane as the separator.

[0043] Example 3

[0044] Weigh out 0.8 g of MnO2 and 0.2 g of PAN. First, dissolve the PAN in 10 mL of DMF and stir until completely dissolved. Add the MnO2 to the PAN solution in three portions, grinding for 10 minutes after each addition in an agate mortar. After all the MnO2 has been added, continue grinding for 30 minutes to obtain a uniform paste. Then transfer the paste to a glass bottle and sonicate it for 30 minutes in an ultrasonic cleaner. Pour the paste onto a polytetrafluoroethylene plate, scrape it into a 1 mm thick layer with a scraper, and vacuum dry at 60°C for 12 hours to obtain the precursor powder.

[0045] The precursor powder was placed in a quartz boat and then placed in a muffle furnace.

[0046] In the first stage, the heating rate is 1℃ / min and the temperature is 180℃.

[0047] In the second stage, the temperature was increased from 180℃ to 260℃ at a rate of 0.5℃ / min. The temperature was maintained for 2 hours, and the product was obtained after cooling.

[0048] The pre-oxidized product was heated to 280°C at a rate of 2°C / min in an argon atmosphere and held at that temperature for 1 hour. After natural cooling, the final material was obtained, denoted as 20% P@MnO2.

[0049] Polyacrylonitrile@manganese dioxide, conductive agent acetylene black, and binder polyvinylidene fluoride were mixed and ground at a mass ratio of 7:2:1, and then coated onto a carbon cloth current collector. The mixture was dried at 80°C for 24 hours to obtain a polyacrylonitrile@manganese dioxide modified cathode material. An aqueous zinc-ion battery was assembled using commercial zinc sheets as the negative electrode, 2 mol / L zinc sulfate as the electrolyte, and a glass fiber membrane as the separator.

[0050] Comparative Example 1

[0051] KMnO4 and MnSO4 were dissolved in 80 mL of pure water at a molar ratio of 4:3 and stirred for 30 min. The mixture was then transferred to a reaction vessel. The temperature was then increased to 160 °C at a rate of 10 °C / min and maintained at this temperature for 12 h. After cooling to room temperature, the mixture was centrifuged and washed eight times with deionized water and anhydrous ethanol to remove residual salts. The solid precipitate was then collected. The powder was dried overnight at 80 °C to obtain powdered MnO2.

[0052] Manganese dioxide, conductive agent acetylene black, and binder polyvinylidene fluoride were mixed and ground in a mass ratio of 7:2:1, and then coated onto a carbon cloth current collector. The mixture was dried at 80°C for 24 hours to obtain the manganese dioxide positive electrode material. An aqueous zinc-ion battery was assembled using commercial zinc sheets as the negative electrode, 2 mol / L zinc sulfate as the electrolyte, and a glass fiber membrane as the separator.

[0053] Material characterization and performance testing:

[0054] The MnO2 material prepared in Comparative Example 1 was observed by SEM, and the results are as follows: Figure 1 As shown, the prepared MnO2 material has a rod-like structure.

[0055] The 10% P@MnO2 composite material prepared in Example 2 above was observed by TEM, and the results are as follows: Figure 2 As shown, the surface of manganese dioxide is coated with polyacrylonitrile, and the coating thickness is 3 nm.

[0056] The polyacrylonitrile@manganese dioxide modified materials prepared in Examples 1-3 and the MnO2 material prepared in Comparative Example 1 were subjected to XRD tests. The XRD patterns shown in the figure are as follows ( Figure 3 It can be clearly seen that, compared with the original manganese dioxide spectrum, the structure of the polyacrylonitrile@manganese dioxide modified material after low-temperature treatment has not changed.

[0057] XPS spectra of O1s and N1s of the 10% P@MnO2 composite material prepared in Example 2 were analyzed. Figure 4 In the XPS N1s spectrum, a novel peak morphology was observed at 399.5 eV, confirming that this peak corresponds to the newly formed Mn-N bond, thus verifying the successful formation of Mn-N bonds between manganese dioxide and polyacrylonitrile due to interfacial interactions. In the XPS O1s spectrum, a new characteristic peak appeared at 531 eV in the composite material, corresponding to the Mn-OC interface bridging oxygen, further demonstrating that covalent bonding has formed between polyacrylonitrile and manganese dioxide.

[0058] The aqueous zinc-ion batteries assembled in Examples 1-3 and Comparative Example 1 were subjected to charge-discharge cycle tests at a rate of 0.5C. Figure 5Different proportions of polyacrylonitrile have different effects on the specific capacity and cycle stability of the battery. In Example 2, the initial capacity of the 10% P@MnO2 composite material battery was 246 Ah / g, and after 100 cycles, it still had a reversible capacity of 213 mAh / g, with a capacity retention rate of about 86.6%. In contrast, the pure MnO2 material prepared in Comparative Example 1 had a first-cycle discharge specific capacity of about 220 mAh / g at a current density of 0.5C, and only a reversible capacity of 123 mAh / g after 100 cycles, with a capacity retention rate of only about 55.9%. It can be seen that its cycle stability is much worse than that of the material prepared in Example 2. For the 20% P@MnO2 composite material in Example 3, under the same conditions, the discharge specific capacity of the battery drops sharply. The first-cycle discharge specific capacity at a current density of 0.5C is about 145 mAh / g. It can be seen that the difference in the ratio of polyacrylonitrile to manganese dioxide will affect the experimental results. When the ratio of the two is in a suitable range (9:1 to 19:1), the coating effect of polyacrylonitrile on manganese dioxide is better, which can effectively improve the structural stability of manganese dioxide and further improve the specific capacity and cycle stability of aqueous zinc-manganese batteries.

[0059] The aqueous zinc-ion battery assembled in Example 2 was subjected to charge-discharge tests at different rates, and the results are as follows: Figure 6 As shown, the aqueous zinc-ion battery assembled in Example 2 discharged at 0.1C, yielded a capacity of approximately 305 mAh / g, and at 2C, it discharged approximately 130 mAh / g. This demonstrates that the zinc-ion battery made with 10% P@MnO2 composite material as the electrode material still exhibits good rate performance at different rates.

[0060] Table 1 shows the ICP test results in zinc sulfate electrolyte for the polyacrylonitrile@manganese dioxide modified materials prepared in Examples 1-3 and the MnO2 material prepared in Comparative Example 1 under the same soaking time conditions. It can be seen that the Mn concentration in the pure MnO2 electrolyte of Comparative Example 1 is the highest, indicating severe manganese leaching in the electrolyte. After PAN coating modification, the manganese leaching concentration is significantly reduced, and the leaching inhibition effect is further enhanced with increasing PAN coating ratio.

[0061] In summary, the material of this invention forms a dense protective layer through interfacial chemical bonding without relying on high-temperature carbonization, thereby inhibiting manganese dissolution, improving cycle stability, and maintaining good rate performance.

[0062]

[0063] Table 1

[0064] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification.

Claims

1. A low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material, characterized in that, The invention includes manganese dioxide particles, the surface of which has a coating layer, the coating layer being cyclized polyacrylonitrile, and the coating layer being chemically bonded to the manganese dioxide via Mn-OC and Mn-N bonds.

2. The low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material according to claim 1, characterized in that, The coating layer has a thickness of 2-20 nm.

3. The low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material according to claim 1, characterized in that, The mass ratio of manganese dioxide to polyacrylonitrile is 9:1 to 19:

1.

4. The method for preparing a low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material according to claim 1, characterized in that, Includes the following steps: Step 1: First, completely dissolve polyacrylonitrile in a polar organic solvent. Then, add manganese dioxide to the polyacrylonitrile solution and grind it to obtain a uniform paste. After ultrasonic treatment of the paste, scrape it into a thin layer and dry it in a vacuum environment at 60°C to obtain the precursor powder. Step 2: Heat the precursor powder at a heating rate of 1℃ / min until it reaches 180℃~200℃. Step 3: Continue heating the precursor powder at a rate of 0.5℃ / min until it reaches 240~260℃. After heating, hold the temperature for 2~3 hours and then cool to obtain the pre-oxidized product. Step 4: The pre-oxidized product is heated in an inert gas environment at a heating rate of 2℃ / min to 280℃~300℃, held for 1~2 hours, and then naturally cooled to obtain manganese dioxide cathode material coated with low-temperature cyclized polyacrylonitrile.

5. The method for preparing a low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material according to claim 4, characterized in that, The mass ratio of manganese dioxide to polyacrylonitrile in step one is 9:1 to 19:

1.

6. The method for preparing a low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material according to claim 4, characterized in that, In step one, the polar organic solvent is N,N-dimethylformamide.

7. The method for preparing a low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material according to claim 4, characterized in that, In step four, the inert gas is argon.

8. The application of the low-temperature cyclized polyacrylonitrile-coated manganese dioxide cathode material according to any one of claims 1-3 in an aqueous zinc-ion battery.